Lactic acid bacteria with probiotic potential producing antimicrobial proteins against methicilin resistant Staphylococcus aureus (MRSA) isolated from Malaysian non-broiler chicken - Alhaji Yusuf, Moshood; Tengku Abdul Hamid, Tengku Haziyamin (2012)
In this study, a domestic non-broiler chicken, other than commonly used broiler chicken, is used as source of Lactic acid bacteria (LAB). LAB were isolated from the ceca, intestine, gizzard and bile of domestic Malaysian non-broiler chicken ‘ayam kampung’. Following incubation on MRS agar plates, 56 LAB isolates were collected. Out of 56 isolates, 5 isolates; L3, L4, L5, L7 and L7 showed inhibition against indicator organism Methylene-Resistant Staphylococcus aureus MRSA. All of the five isolates show Gram positive coccus morphology, non-spore forming, catalase negative, producing CO2 and acid from glucose. They are able to grow on 4, 6 and 10% NaCl as typical characteristics of Enterococcus family. Ability to produce inhibitory proteins was tested using purified fraction from Three Phase Partitioning (TPP) employing t-butanol and ammonium sulphate. The purified fraction produced zones of inhibition on the indicator organism of sizes as large as 18 mm in diameter based on disk diffusion method. The purified fraction contained putative low molecular weight proteins of about 10 kDa in size as determined by SDS-PAGE. This putative proteins was stable upon heat treatment and it was inactivated by trypsin. The amplified rDNA gene from the 5 isolates were subsequently sequenced and their partial sequences showed to be at least 98% similarity with those of Enterococcus family. Isolate L3, L4, and L5 were found to be belonged to the E. faecum. Meanwhile, L7 and L10 belonged to E. faecalis and E. mundtii, repsectively. These probiotic strains, exclusively isolated from non-broiler chicken, produced putative inhibitory proteins or bacteriocins against Staphylococcus aureus MRSA.